Square-Trigonometry Equations!

Geometry Level 2

1 sin 2 θ 1 cos 2 θ 1 tan 2 θ 1 cot 2 θ 1 sec 2 θ 1 csc 2 θ = 3 \dfrac1{\sin^2{\theta}}-\dfrac1{\cos^2{\theta}}-\dfrac1{\tan^2{\theta}}-\dfrac1{\cot^2{\theta}}-\dfrac1{\sec^2{\theta}}-\dfrac1{\csc^2{\theta}}=-3

Find the number of solutions of θ \theta in the interval ( 0 , 2 π ) (0,2\pi) that satisfy the equation above.


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ikkyu San
Aug 23, 2015

1 sin 2 θ 1 cos 2 θ 1 tan 2 θ 1 cot 2 θ 1 sec 2 θ 1 csc 2 θ = 3 csc 2 θ sec 2 θ cot 2 θ tan 2 θ cos 2 θ sin 2 θ = 3 ( csc 2 θ cot 2 θ ) sec 2 θ tan 2 θ ( cos 2 θ + sin 2 θ ) = 3 1 ( 1 + tan 2 θ ) tan 2 θ 1 = 3 1 tan 2 θ tan 2 θ = 3 2 tan 2 θ = 2 tan 2 θ = 1 tan θ = ± 1 \begin{aligned}\dfrac1{\sin^2{\theta}}-\dfrac1{\cos^2{\theta}}-\dfrac1{\tan^2{\theta}}-\dfrac1{\cot^2{\theta}}-\dfrac1{\sec^2{\theta}}-\dfrac1{\csc^2{\theta}}=&\ -3\\\csc^2{\theta}-\sec^2{\theta}-\cot^2{\theta}-\tan^2{\theta}-\cos^2{\theta}-\sin^2{\theta}=&\ -3\\(\csc^2{\theta}-\cot^2{\theta})-\sec^2{\theta}-\tan^2{\theta}-(\cos^2{\theta}+\sin^2{\theta})=&\ -3\\1-(1+\tan^2{\theta})-\tan^2{\theta}-1=&\ -3\\-1-\tan^2{\theta}-\tan^2{\theta}=&\ -3\\-2\tan^2{\theta}=&\ -2\\\tan^2{\theta}=&\ 1\\\tan{\theta}=&\ \pm1\end{aligned}

Thus,

{ tan θ = 1 θ = π 4 , 5 π 4 tan θ = 1 θ = 3 π 4 , 7 π 4 \begin{cases}\tan{\theta}=1\Rightarrow\theta=\dfrac{\pi}4,\dfrac{5\pi}4\\\tan{\theta}=-1\Rightarrow\theta=\dfrac{3\pi}4,\dfrac{7\pi}4\end{cases}

Hence, This equation has 4 \boxed4 solutions in the interval ( 0 , 2 π ) (0,2\pi) .

Or you can note that there is one solution for each quadrant. Since we're covering all four quadrant, then there is 4 solutions.

Pi Han Goh - 5 years, 9 months ago
Lixin Zheng
May 7, 2017

1 sin 2 θ 1 cos 2 θ 1 tan 2 θ 1 cot 2 θ 1 sec 2 θ 1 csc 2 θ = 3 \dfrac1{\sin^2{\theta}}-\dfrac1{\cos^2{\theta}}-\dfrac1{\tan^2{\theta}}-\dfrac1{\cot^2{\theta}}-\dfrac1{\sec^2{\theta}}-\dfrac1{\csc^2{\theta}}=-3 Writing this in terms of sin θ \sin{\theta} and cos θ \cos{\theta} , we obtain 1 sin 2 θ 1 cos 2 θ cos 2 θ sin 2 θ sin 2 θ cos 2 θ cos 2 θ sin 2 θ = 3 \dfrac1{\sin^2{\theta}}-\dfrac1{\cos^2{\theta}}-\dfrac{\cos^2{\theta}}{\sin^2{\theta}}-\dfrac{\sin^2{\theta}}{\cos^2{\theta}}-\cos^2{\theta}-\sin^2{\theta}=-3 Subsitute all sin 2 θ \sin^2{\theta} with x x and cos 2 θ \cos^2{\theta} with 1 x 1-x , we obtain 1 x 1 1 x 1 x x x 1 x ( 1 x ) x = 3 \dfrac1{x}-\dfrac1{1-x}-\dfrac{1-x}{x}-\dfrac{x}{1-x}-(1-x)-x=-3 1 x x x 2 x x x 2 1 2 x + x 2 x x 2 x 2 x x 2 1 = 3 \dfrac{1-x}{x-x^2}-\dfrac{x}{x-x^2}-\dfrac{1-2x+x^2}{x-x^2}-\dfrac{x^2}{x-x^2}-1=-3 1 x x 1 + 2 x x 2 x 2 x x 2 = 2 \dfrac{1-x-x-1+2x-x^2-x^2}{x-x^2}=-2 2 x 2 x x 2 = 2 \dfrac{-2x^2}{x-x^2}=-2 Multiplying on both sides, we get 2 x 2 = 2 x + 2 x 2 -2x^2=-2x+2x^2 4 x 2 2 x = 0 4x^2-2x=0 Factoring yields 2 x ( 2 x 1 ) = 0 2x(2x-1)=0 x = 0 , 1 2 x=0,\frac{1}{2} Recall that sin 2 θ = x \sin^2{\theta}=x , so s i n 2 θ = 0 , 1 2 sin^2{\theta}=0, \frac{1}{2} , and sin θ = 0 , ± 1 2 \sin{\theta}=0, \pm\dfrac{1}{\sqrt{2}} . However, sin θ \sin{\theta} cannot equal 0 0 because then sin 2 θ \sin^2{\theta} would be 0 0 and 1 sin 2 θ \dfrac{1}{\sin^2{\theta}} would be undefined. Therefore sin θ \sin{\theta} must equal ± 1 2 \pm\dfrac1{\sqrt{2}} or 2 2 \dfrac{\sqrt{2}}{2} . Therefore θ \theta must have 4 \boxed{4} solutions: π 4 , 3 π 4 , 5 π 4 , a n d 7 π 4 \dfrac{\pi}{4}, \dfrac{3\pi}{4}, \dfrac{5\pi}{4}, and \dfrac{7\pi}{4} .

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...